A rare case report: Acquired vulva lymphangioma in a young female post tubercular lymphadenitis - Marissa Astari; Afif Nurul Hidayati (PAGEPress Publications, 2019)
Lymphangioma are rare benign proliferations of the lymphatic system. Acquired lymphangioma circumscriptum of the vulva is a superficial lymphatic malformation, presenting as lymph-filled micro-to macroscopic vesicles. We describe a rare case of acquired vulva lymphangioma resulting from tubercular lymphadenitis. A 20-year-old female came to Dermatology and Venereology Outpatient Clinic of Dr. Soetomo General Hospital with chief complain there were multiple clusters vesicles on her genitalia since three months ago. The vesicles followed with discomfort and slightly itchy. There was a lymphedema on both of her inguinal since 5 years ago. She was diagnosed with tubercular lymphadenitis in 13 years old of age. No history of sexual transmitted disease. She had 5 times of cryotherapy and it nearly got remission.